The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/hr/uhac225
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning to explore the genomic prediction accuracy of fall dormancy in autotetraploid alfalfa

Abstract: Fall dormancy (FD) is an essential trait to overcome winter damage and for alfalfa (Medicago sativa) cultivar selection. The plant regrowth height (PRH) after autumn clipping is an indirect way to evaluate FD. Transcriptomics, proteomics, and QTL mapping have revealed crucial genes correlated with FD, however, these genes can’t predict alfalfa FD very well. Here, we conducted genomic prediction of FD using whole genome SNP markers based on machine learning-related methods support vector machines (SVM) regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…Because when the amount of data is large with many missing values, and the number of independent variables is much larger than the sample size, the traditional Cox regression forward, backward, and stepwise method may not be applicable. In addition to these methods, the random forest, Support Vector Machine, principle component analysis, 33 deep learning, and extreme gradient boosting of machine learning are also becoming much popular 32,34,35 . Machine learning are more robust and can outfit imbalanced datasets 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because when the amount of data is large with many missing values, and the number of independent variables is much larger than the sample size, the traditional Cox regression forward, backward, and stepwise method may not be applicable. In addition to these methods, the random forest, Support Vector Machine, principle component analysis, 33 deep learning, and extreme gradient boosting of machine learning are also becoming much popular 32,34,35 . Machine learning are more robust and can outfit imbalanced datasets 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This model is mainly and widely used for the prognostic analysis of tumors and other chronic diseases, and can also be used for etiology exploration in cohort studies. For high‐dimensional and multicollinear data, Lasso, Ridge, and ElasticNet regressions are more suitable 31,32 . Because when the amount of data is large with many missing values, and the number of independent variables is much larger than the sample size, the traditional Cox regression forward, backward, and stepwise method may not be applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that for all traits, the prediction accuracies using subsets of SNPs were generally slightly higher as compared to that of using all SNPs. Several previous studies showed that a larger number of random SNPs reduced prediction accuracy in GS as compared to the SNPs derived from GWAS studies (Alemu et al, 2021;Singer et al, 2022;Spindel et al, 2016;Yan et al, 2023;Zhang et al, 2022). This high prediction appeared to be common in GS regardless of traits of interest in alfalfa (Zhang et al, 2022) and other crops such as maize (Rice & Lipka, 2019;Yan et al, 2023), wheat (Triticum aestivum L.) (Alemu et al, 2021;Arruda et al, 2016), rice (Oryza sativa L.) (Spindel et al, 2016) There is also a concern about the overestimation of prediction accuracy in the GWAS-derived approach.…”
Section: Effectiveness Of Snps Selection Methodsmentioning
confidence: 99%
“…Several previous studies showed that a larger number of random SNPs reduced prediction accuracy in GS as compared to the SNPs derived from GWAS studies (Alemu et al, 2021;Singer et al, 2022;Spindel et al, 2016;Yan et al, 2023;Zhang et al, 2022). This high prediction appeared to be common in GS regardless of traits of interest in alfalfa (Zhang et al, 2022) and other crops such as maize (Rice & Lipka, 2019;Yan et al, 2023), wheat (Triticum aestivum L.) (Alemu et al, 2021;Arruda et al, 2016), rice (Oryza sativa L.) (Spindel et al, 2016) There is also a concern about the overestimation of prediction accuracy in the GWAS-derived approach. Alemu et al (2021) reported that wrr-BLUP method (weighted ridge regression BLUP) could overestimate the GS accuracy due to individuals' inclusion in both the GWAS and test populations.…”
Section: Effectiveness Of Snps Selection Methodsmentioning
confidence: 99%
See 1 more Smart Citation